Imaging and surgical predictive factors for postoperative hemorrhage after partial nephrectomy and clinical results of trans-arterial embolization. Issue 3 (22nd January 2021) - Qin, Caipeng; Zhi, Xin; Wang, Fei; Li, Qing; Gao, Jian; Liu, Shijun; Xu, Tao
Abstract : Abstract: Partial nephrectomy (PN) has been established as the standard treatment for T1 renal tumors, and postoperative hemorrhage due to vascular complications is a rare but potentially life-threatening complication reported after PN. Thus, this study evaluated the imaging and surgical factors associated with postoperative hemorrhage after PN and the clinical results of trans-arterial embolization. A retrospective review of the institutional PN database was performed from May 2012 to January 2019, revealing that we performed 810 PN procedures at our institution. In total, 12 patients were referred to the interventional radiology department for vascular complications after the procedure. Patients with and without transarterial embolization (TAE) were age- and sex-matched with 56 patients. Preoperative imaging characteristics and operative details were considered. Univariable and multivariable analyses were used to test their eventual association with the occurrence of hemorrhage. Furthermore, renal functions at diagnosis, after operation or embolization for TAE cases, and at the last follow-up were recorded. A diagnosis of hemorrhage was made at a median of 4 (range, 0–25) days after surgery. The majority of patients (50%) presented with gross hematuria. T test revealed higher renal tumor-parenchyma contact area (TPA) ( P = .0407), Length-A ( P = .0136), Length-P ( P = .0267), operation time ( P = .0214) and estimated blood loss ( P = .0043) in patients with hemorrhage than in controls. Binary logistic regression analysis identified TPA ( P = .048) and estimated blood loss ( P = .042) as independent predictors for postoperative hemorrhage with an area under the ROC curve of 0.705 (64% sensitivity and 79% specificity). In conclusion, the occurrence of hemorrhage after PN was associated with a larger TPA and more estimated blood loss during the procedure. In patients who underwent selective TAE, renal function remained comparable with that of controls.